An Integrated Lipidomics and Phenotype Study Reveals Protective Effect and Biochemical Mechanism of Traditionally Used Alisma orientale Juzepzuk in Chronic Kidney Disease - Dou, Fang; Miao, Hua; Wang, Jing-Wen; Chen, Lin; Wang, Ming; Chen, Hua; Wen, Ai-Dong; Zhao, Ying-Yong (Frontiers in Pharmacology, 2018)
Alisma orientale Juzepzuk (AO) is widely used for various diuretic and nephropathic treatments in traditional Chinese medicines. In a clinical setting, AO is used as both a lipid-lowering and tubular interstitial fibrosis agent. However, the mechanisms of AO for the treatment of renal interstitial fibrosis and abnormal lipid metabolism are not well understood. In this study, pharmacological and UPLC-HDMS-based lipidomic approaches were employed to investigate the lipid-lowering and tubular interstitial fibrosis effect of AO on rats with adenine-induced chronic kidney disease (CKD). Rats with CKD showed increased serum levels of creatinine and urea, tubular damage, and tubular interstitial fibrosis. Moreover, multiple lipid species were identified in CKD rats. Among these lipids, polyunsaturated fatty acid, eicosapentaenoic acid, 8,9-epoxyeicosatrienoic acid, and docosahexaenoic acid levels were significantly decreased in CKD rats compared to control rats. In CKD rats, up-regulation of the NF-κB pathway may impair polyunsaturated fatty acid metabolism, causing renal fibrosis. In addition, CKD rats showed significantly decreased diglyceride levels and increased triglyceride levels compared to the control group. Pathway over-representation analysis demonstrated that 30 metabolic pathways were associated with lipid species. AO treatment suppressed up-regulation of inflammation, and partly restored the deregulation of polyunsaturated fatty acids and glycerolipids metabolism. Our results indicated that AO treatment attenuated renal fibrosis by down-regulating inflammation, and mitigating lipid metabolism in CKD rats. In conclusion, this study has identified the therapeutic lipid-lowering and anti-fibrosis effects of AO on CKD.